Light-induced quantum friction of carbon nanotubes in water - Tanuja Kistwal; Krishan Kanhaiya; Adrian Buchmann; Chen Ma; Jana Nikolić; Julia Ackermann; Phillip Galonska; Sanjana S. Nalige; Vahideh Sardari; Aishwarya Sudarsan; Martina Havenith; Marialore Sulpizi; et al. (Nature, 2026)
Abstract Friction slows down moving objects at both macroscopic and microscopic scales 1 . At the electronic level, quantum friction describes direct transfer of momentum between a liquid and the electrons of a solid 2 . Owing to its microscopic nature, this phenomenon remains experimentally challenging to capture 3 . Here we show that near-infrared fluorescent single-walled carbon nanotubes (SWCNTs) exhibit light-induced quantum friction in water. It is measured by observing an excitation-power-dependent linear decrease of around 50% in the diffusion constants of functionalized SWCNTs in aqueous solution. This effect disappears when excitons are localized, as in the case of SWCNTs with quantum defects. We further show that the chemical manipulation of exciton concentration by molecules that increase or decrease SWCNT fluorescence also modulates the diffusion constant by up to a factor of 2. Optical pump terahertz (THz) probe spectroscopy shows an instantaneous response (around 30 cm −1 ) that we assign to direct exciton–water coupling in the range of water Debye modes. It is followed by an increasing (>100 ps) response in the range of intermolecular translational modes of the hydrogen bond network of water (>100 cm −1 ), resembling heating. Classical molecular dynamics simulations further support a mechanism in which the fluctuating dipole moments of excitons create frictional forces. These findings establish light-induced quantum friction between excitons in SWCNTs and water and show that electronic excitations can be used to control nanoscale motion and fluid properties.